Impact of Human Resource Management Practices on Employees’ Behavioural Outcomes in the Manufacturing Sub-Sector of South-West Nigeria - Onikoyi, Idris Adegboyega; Omoyele, Oluwfemi Samuel; Odumeru, James Adetunji; Odeh, Callistus Destiny (Acta Universitatis Danubius. Œconomica, 2023)
Most authors agree that Human Resources is the most important input available to any organisation. As such, scholars generally believe that Human Resource Management (HRM) practices have positive impact on firm performance. This belief is hinged on the fact that positive HRM practices strengthen competence, motivation, commitment and other employee outcomes leading to an improved organisational performance. However, there exists limited empirical evidence that connects HRM practices to employee outcomes. This study investigated the impact of HRM practices on competence, commitment, job satisfaction, motivation, cooperation with management, cooperation with co-workers, employee presence and compliance in the manufacturing sub-sector of South – Western Nigeria. To achieve this objective, the study adopted cross sectional survey research design where data was collected from 381 middle level managers of manufacturing companies in Lagos, Nigeria selected using stratified and random sampling techniques. Data were analysed using Structural Equation Modelling (SEM). Results show that HRM practices determine and predict components of employee outcomes. In other words, recruitment and selection, training and development, performance appraisal, compensation management, occupational health and safety and career growth and development all determine competence, commitment, job satisfaction, motivation, cooperation with management, cooperation with co-workers, presence and compliance all in varying degrees. The study justified investment in HRM and therefore recommends bundled approach to the application of HRM practice. Other results are and implications are discussed in the article.